Positive and Negative Sides of IT Consumerization from the Company’s Point of View - Petrović, Marijana (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
IT consumerization is a phenomenon that has caused a change in people’s behavior and expectations of the technology they use, which has spilled over into all their spheres of life, including work. Consequently, organizations had to find ways to adapt to this, in order to attract and retain tech-savvy employees. The COVID-19 pandemic has forced companies to accelerate the provision of work from home on a larger scale, which is actually one of the aspirations and opportunities of employees in the era of IT consumerization. This paper helps to understand the impact that IT consumerization has on companies. Its positive and negative sides are presented through the impact on employees, technology, processes and data in order to draw attention to the consequences of this phenomenon and its potential dangers and opportunities.